2017
DOI: 10.1161/hypertensionaha.116.08158
|View full text |Cite
|
Sign up to set email alerts
|

Development of Left Ventricular Hypertrophy in Treated Hypertensive Outpatients

Abstract: L eft ventricular (LV) hypertrophy (LVH) is a marker of target organ damage in hypertension and helps stratifying cardiovascular risk.1,2 The effect of LVH on incident cardiovascular events is independent of conventional risk factors and of coronary artery disease. [3][4][5] In selected subsets of nondiabetic patients, LVH also precedes new onset of diabetes mellitus, 6 suggesting that hypertensive target organ damage might be also a marker of complex metabolic changes associated with the evolution of art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 45 publications
5
29
0
2
Order By: Relevance
“…If, when, and how often the assessment of HMOD should be performed has not been validated in follow-up studies. HMOD can also develop during the course of antihypertensive treatment [185], and this may be accompanied by increased risk [186][187][188].…”
Section: Hypertension-mediated Organ Damage Regression and Cardiovascmentioning
confidence: 99%
“…If, when, and how often the assessment of HMOD should be performed has not been validated in follow-up studies. HMOD can also develop during the course of antihypertensive treatment [185], and this may be accompanied by increased risk [186][187][188].…”
Section: Hypertension-mediated Organ Damage Regression and Cardiovascmentioning
confidence: 99%
“…Development of LVH is a complex and multifactorial process which involves genetic, hemodynamic and anthropometric components, neuro-hormonal stimulation, growth factors and inflammatory mediators [53][54][55]. The hemodynamic and metabolic disorders associated with insulin resistance increase the risk LVH.…”
Section: Left Ventricular Hypertrophymentioning
confidence: 99%
“…Another recent large study from Italy evaluated 4920 patients with treated HTN and no LVH at baseline, and found that baseline obesity status predicted development of incident LVH at 48 month follow up. 62 Following the myriad of known CV complications, smoking is also related with LVH. In the large MESA study mentioned previously, of 4,869 patients evaluated by CMR, current smokers had an average increase in LVM of 7.7g over non-smokers.…”
Section: Risk Factors For Lvhmentioning
confidence: 99%